Prolegômenos a uma arqueologia da música: saber e modernidade musical - Silva, Thiago Cazarim da (2011)
The aim of this work is to unfold a suggestion given by Michel Foucault, which indicates the possibility of applying the archeological method to a philosophical approach to the arts, literature and as we tried to do throughout this research to music as well. For this purpose, have been taken not only the works in which Foucault have described or developed his archeology (e.g. L archeologie du savoir, L ordre du discourse), but also some texts that Deleuze, Merleau-Ponty and Foucault himself wrote about literature, cinema and the arts. Theses texts, I argue, could point out some decisive and distinctive features of Musical Modernity. Therefore, they could serve to establish the philosophical boundaries into which an archeological description of music should move; consequently, they should show the differences between an archeological and some musicological approaches to become helpful to the comprehension of the very interest of a History of Music.